Post-Disaster Reconstruction: Meeting Stakeholder Interests Proceedings of a Conference held at theScuola di Sanità Militare, Florence, Italy17-19 May 2006 - Alexander, David; Davidson, Colin Henry; Fox, Andrew; Lizzaralde, Gonzalo; Johnson, Cassidy (Atti, 2007)
This book collects together 46 papers presented at the Third Biennial Conference of i-Rec, International Group for the Diffusion of Research and Information on Post-Disaster Reconstruction. The various sections of the book cover the technical and administrative aspects of housing and other buildings after disaster. The approach to post-disaster shelter and reconstruction exemplified by this volume is fully interdisciplinary. A very wide range of perspectives is covered, including the disciplines and sub-disciplines of seismic and structural engineering, architecture, applied geography and geology, environmental psychology, paediatrics, development studies, economics, medicine and public health, management studies and political science. The volume is also intended to commemorate the 40th anniversary of the floods that severely damaged Florence in 1966 and did terrible damage to priceless art treasures.